How the operationalization of exposure impacts studies on direct-to-consumer advertising of prescription drugs - Savelli, Melanie R. (International Journal of Pharmaceutical and Healthcare Marketing, 2020)
Purpose: Without having a shared operationalization of what constitutes a direct-to-consumer advertising (DTCA) exposure, it is impossible to accurately generalize findings about their effects. First, it needs to be established how the variables involved in exposures impact outcomes. This will allow for more accurate operationalizations. Design/methodology/approach: A sample of 216 participants were recruited from Amazon’s Mechanical Turk and randomly assigned into one of four conditions to take an online survey. A 2 × 2 experiment (active/passive attention × low/high exposure) was conducted to determine if the level of attention, otherwise known as attentiveness, and the number of exposures impacted preferences for a fictitious prescription sleep aid. Findings: Results indicated a significant difference among active and passive conditions such that active exposures resulted in stronger positive preferences. Research limitations/implications: Studies using different operationalizations should not be aggregated for generalizations about the effects of DTCA of prescription drugs. Originality/value: This paper urges researchers to clearly operationalize their definitions for “exposure” and to be hesitant about generalizing findings studies using different definitions. © 2020, Emerald Publishing Limited.
Keywords: Advertising; Direct-to-consumer; Exposure; Pharmaceutical marketing; Prescription drugs; dept.com; peer-reviewed

Measuring the Impact of Cause-Related Marketing: A Meta-Analysis of Nonprofit and For-profit Alliance Campaigns - Rego, Michelle M.; Hamilton, Mark A.; Rogers, Dana (Journal of Nonprofit & Public Sector Marketing, 2020)
Keywords: dept.com; peer-reviewed

Mentoring, sponsorship, and gender - Burke, Karen P.; Ciccomascolo, Lori E. (Social Justice and Putting Theory Into Practice in Schools and Communities, 2020)
The lack of women in leadership roles is a systemic problem in the United States and is not unique to the field of education; however, it is important to continue to challenge the status quo and provide a path for women to achieve equality and equity in the workplace. The following chapter will identify and discuss the importance of mentoring and sponsorship so that women pursuing education careers, novice women teachers, and women college, and university faculty and staff can actively and better position themselves to move into leadership positions and/or ensure a “seat at the table” in situations where decisions are made that affect their personal and professional lives.
Keywords: dept.com